ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP PERMINTAAN SAYURAN HIDROPONIK PADA FOREVER GREEN HYDROPONIC FARM JAKARTA TIMUR - Febriana, Febriana; Handayani, Migie; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
ABSTRACTHydroponic vegetables are an agricultural commodity that has promising business opportunities. Demand for hydroponic vegetables continues to increase due to increasing public awareness about healthy lifestyles. The study aimed to analyze the marketing mix and analyze the impact of marketing mix on the demand for hydroponic vegetables. The research was conducted in Forever Green Hydroponic Farm, Duren Sawit, East Jakarta. This research used case study method with a quantitative descriptive approach. The sampling method used non-probability namely purposive sampling. The number of sample is 100 respondents who were end customers, aged 17 years and over, and had purchased hydroponic vegetables at Forever Green at least once. Secondary data collection was carried out using interview techniques with questionnaire tools and observation while primary data was obtained from various studies and relevant literature. The data analysis method used was descriptive analysis and multiple linear regression analysis. The bebast variable in this study was the marketing mix which consists of product, price, distribution, and promotion while the terikatt variable used was the demand of hydroponic vegetables in Forever Green Hydroponic Farm. The results of this study showed that the variables of products, prices, places, and promotions simultaneously had a very significant effect on the hydroponic vegetable demand at Forever Green Hydroponic Farm. Partially the variables of product, price, and distribution have a significant effect on the hydroponic vegetable demand, while the variable of promotion has no effect on the hydroponic vegetable demand at Forever Green Hydroponic Farm.